Prevalence and causes of bilateral visual impairment in rural areas of Tianjin, China – The Tianjin Eye Study. Issue 2 (29th June 2020) - Meng, Xiangda; Zhou, Wei; Sun, Zhuoyu; Han, Qi; Zhang, Jingkai; Zhang, Hongwen; Wang, Weijuan; Zhong, Min; Wang, Meiyan; Zhang, Junlan; Hao, Jing; Han, Han; et al.
Abstract: Purpose: To estimate the prevalence, causes and risk factors of bilateral visual impairment in rural areas of Tianjin, China. Methods: A large population‐based, cross‐sectional study. A stratified random cluster sampling method was used to investigate 12 233 participants in all age groups living in rural Tianjin. Participants completed questionnaires and received professional ophthalmology examinations. Results: According to World Health Organization best‐corrected visual acuity (BCVA) criteria, the crude prevalence of bilateral visual impairment (BCVA < 20/63), bilateral low vision (BCVA < 20/63 to ≥20/400) and bilateral blindness (BCVA < 20/400) was 2.53%, 2.40% and 0.14% (age‐ and gender‐standardized prevalence was 1.86%, 1.76% and 0.11%). The prevalence increased with age and was higher in women than men. The most common causes of bilateral visual impairment in the total population were cataract (48.39%), refractive error/amblyopia (17.74%), age‐related macular degeneration (AMD) (10.00%), diabetic retinopathy (5.81%) and glaucoma (3.87%). For participants younger than 50 years, refractive error/amblyopia was the leading cause of low vision and blindness, while cataract was the major cause in the participants over 50. Female gender, older age and self‐reported diabetes were associated with increased risks of visual impairment. Conclusion: The age‐ and gender‐standardized prevalence of low vision, especially in the older group (50+), was higher in this study compared with previous studies in China. Refractive error/amblyopia was the leading cause of bilateral visual impairment in younger group, while cataract was the primary cause in the older group. These findings will provide useful information for planning comprehensive eye healthcare programmes in China.